The Formulation of Good Governance Fiqh for Indonesia as a Welfare State - Muhammad Solikhudin; Moh. Zainullah (Institut Agama Islam Negeri Kerinci, 2022)
This study departs from the fact that fiqh, which is the religious guideline for Muslims, does not yet contain specific formulations of good governance that are relevant and increasingly needed in today's state life, especially for Indonesian moslem. This study is intended to identify the principles of good governance and formulate them by looking at their relevance to Indonesia in the context of the welfare state. For that purpose, this study uses the documentation method by collecting and interpreting qualitative data from fiqh books, the 1945 Constitution, and relevant laws and regulations in Indonesia. This study shows that in fiqh books that contain discussions or allude to citizenship and state administration, there are principles of deliberation, justice, welfare, and mutual benefit. These principles can be formulated as good governance fiqh that is relevant to Indonesia which contains the principles of legal certainty, legal urgency, and legal universality. Legal certainty includes accountability and justice. The legal urgency includes aspects of transparency and professionalism. While the universality aspect of law is in the form of guaranteeing general welfare and mutual benefit.